Halide Double‐Perovskite Light‐Emitting Centers Embedded in Lattice‐Matched and Coherent Crystalline Matrix. (27th February 2020) - Dai, Chen‐Min; Zhang, Tao; Wu, Yu‐Ning; Chen, Shiyou
Abstract: Through first‐principles calculations, it is found that two lattice‐matched halide double‐perovskites, Cs2 NaBiBr6 and Cs2 AgBiBr6, have a type‐I band alignment and can form highly miscible alloys in which the disordering makes the bandgaps become direct and activates the direct transition from the valence to conduction band edge, leading to a strong optical absorption and high radiative recombination rate. The bandgaps of the alloys are tunable in a wide range of 1.93–3.24 eV, while the lattice constants remain unchanged. This advantage inspires the design of a coherent crystalline matrix based on Cs2 (Na, Ag)BiBr6 alloys, in which the Ag‐rich and narrower‐bandgap regions are embedded in the Na‐rich and wide‐bandgap region with lattice‐matched and coherent interfaces. The type‐I band alignment drives the photogenerated excitons into the narrower‐bandgap Ag‐rich regions, so the regions become light‐emitting centers with a high photoluminescence quantum yield (PLQY). The bandgaps of the Ag‐rich regions are tunable, so the color of emitted light can be adjusted, making a broadband emission possible. Such kind of coherent crystalline matrix with high‐PLQY and broadband emission can also be fabricated based on the alloys of other lattice‐matched halide double‐perovskites, demonstrating the flexibility of band structure engineering in the coherent heterostructures of various halide double‐perovskites. Abstract : Through embedding narrower‐bandgap alloys in wide‐bandgap alloys, a coherent crystalline matrix based on the alloys of two lattice‐matched halide double‐perovskites, such as Cs2 (Na, Ag)BiBr6 alloys, are fabricated and a high photoluminescence quantum yield and broadband light emission are achieved, which demonstrates the flexibility of band structure engineering in coherent heterostructures of various halide double‐perovskites.